O-34 Hereditary or inflammatory childhood neuropathy – Electrophysiological abnormalities helpful in the differentiation. Issue 7 (July 2019) - Lukawska, Malgorzata; Potulska-Chromik, Anna; Kochanski, Andrzej; Kabzinska, Dagmara; Gawel, Małgorzata; Seroka, Andrzej; Kostera-Pruszczyk, Anna
Abstract : Background: The differentiation between hereditary neuropathy and chronic inflammatory demyelinating polyneuropathy (CIDP) in children is especially significant because of completely different treatment possibilities and prognosis in these conditions. The aim of the study was to compare electrophysiological abnormalities in a group of children and young adults with demyelinating neuropathy of chronic or subacute onset. Material and methods: Retrospective analysis of clinical and nerve conduction study (NCS) data included 3 children and 4 young adults with Charcot-Marie-Tooth Neuropathy X type 1 (CMTX1), 24 children with Charcot-Marie-Tooth Neuropathy type 1a (CMT1a), 8 with hereditary neuropathy with pressure palsy (HNPP) and 18 children with CIDP. Results: In our study 6/7 CMTX1 had both axonal and demyelinating changes in NCS study. The AAN and EFNS electrophysiological CIDP criteria were fulfilled in 2/7 CMTX1, 23/24 CMT1a, 4/8 HNPP and 17/18 CIDP patients. Additionally 3 patients with CMTX1 are classified with EFNS criteria as "probable/possible CIDP". A distal compound muscle action potential (dCMAP) was >9 ms in all CMT1a and 14/18 CIDP patients but none with CMTX1 nor HNPP. Abnormal median/normal sural SNAP (AMNS) or while abnormal sural/normal median SNAP (ASNM) parameter and a difference between conduction velocities (CV) of two corresponding nerves > 10 m/s were not observed in any CMT1a patient. Conclusion: Our study has showed that presented above electrophysiological parameters are useful in differentiation between these neuropathies.